2001
DOI: 10.1063/1.1331338
|View full text |Cite
|
Sign up to set email alerts
|

Electrical and structural properties of solid phase crystallized polycrystalline silicon and their correlation to single-electron effects

Abstract: Single-electron transistors have been fabricated in solid phase crystallized polycrystalline silicon films deposited on SiO 2 layers grown on silicon substrates. The single-electron transistors consist of lateral side-gated nanowires. A Coulomb staircase is observed at 4.2 K, which is fully modulated by the side-gate voltage. Two-period conductance oscillations are observed in nanowires fabricated on 10-nm-thick buried oxide layers, while single-period oscillations are observed in nanowires fabricated on 40-nm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
20
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 23 publications
0
20
0
Order By: Relevance
“…29 for details͒. The nanowire was 1 m long and 60 nm wide and the side gates to the nanowire separation were 120 nm ͑Fig.…”
Section: B Fabrication Of Setsmentioning
confidence: 99%
“…29 for details͒. The nanowire was 1 m long and 60 nm wide and the side gates to the nanowire separation were 120 nm ͑Fig.…”
Section: B Fabrication Of Setsmentioning
confidence: 99%
“…Transmission electron microscopy ͑TEM͒ indicated that the grains were columnar with lateral size of 20-150 nm and that the GBs were no thicker than 1 nm. 7 The bulk film was characterized electrically using a large-area ͑100 m contact spacing͒ transmission-line mode ͑TLM͒ test structure. Nanowire structures ͑30 nm wide and 20 nm-80 nm long͒ were used to investigate the microscopic properties over a few GBs.…”
mentioning
confidence: 99%
“…It is known that impurity diffusion in GBs is greater than in crystalline grains. 7,9,10 We therefore attribute the third region to oxygen diffusion in the GBs. Table I shows the silicon thickness consumed by the surface oxide (d s ) and the GB oxygen diffusion length (l GB ).…”
mentioning
confidence: 99%
“…We have reported previously the film microstructure for the poly-Si film [7]. The Raman spectra showed a sharp peak corresponding to crystalline silicon grains at ~ 520 cm -1 and a broad peak at A16.2.2 ~500 cm -1 .…”
Section: Results and Discussion Film Structurementioning
confidence: 83%